2017
DOI: 10.56059/jl4d.v4i1.163
|View full text |Cite
|
Sign up to set email alerts
|

Mobile learning: readiness and perceptions of teachers of Open Universities of Commonwealth Asia

Abstract: Integration of ‘Mobile Learning’ (m-learning) in Open and Distance Learning (ODL) system can play a crucial role in reducing the ‘Digital Divide’ and strengthening ‘Democratization of Education’ by providing quality educational opportunities and access to information quickly at affordable cost in Commonwealth Asian countries. Successful implementation of m-learning will be determined by readiness and positive perception of the teachers towards it. This study examined the m-learning readiness and perception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…In other words, one of the most important prerequisites for the integration of M-learning in to science teaching already existed consequently; the possibility of using M-learning to leverage the achievement in science is high. This result is consistent with that of the study conducted by (Miglani and Awadhiya, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In other words, one of the most important prerequisites for the integration of M-learning in to science teaching already existed consequently; the possibility of using M-learning to leverage the achievement in science is high. This result is consistent with that of the study conducted by (Miglani and Awadhiya, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Results showed that both the instructors and students had high levels of perceptions and acceptance of M-learning. Miglani and Awadhiya (2017) carried out a survey study to determine university teachers' readiness and perceptions of M-learning. The study was conducted among 102 teachers selected across five Commonwealth Asian countries.…”
mentioning
confidence: 99%
“…Kesiapan guru dalam penerapan mobile learning dianggap kurang baik, karena item pada indikator ini relatif sulit disetujui. Kesiapan dalam mobile learning dikategorikan ke dalam kesiapan perangkat dan kesiapan keterampilan (Miglani & Awadhiya, 2017). Kesiapan belajar guru dipengaruhi oleh tingkat pengetahuan teknis, kesadaran dan motivasi (Ismail et al, 2013).…”
Section: Penghalang Penggunaan Smartphone DI Kelasunclassified
“…Hal ini kerana kemahiran guru untuk menggunakan teknologi maklumat dan komunikasi dilihat sebagai satu kayu ukur kerana generasi masa kini yang mesra gajet dan alat komunikasi (Maimun Aqsha, Wan Nurul Syuhada & Mohd Isa, 2017). Kesediaan kemahiran penggunaan M-pembelajaran dinilai berdasarkan aktiviti pengajaran dan pembelajaran yang dilakukan melalui kemudahan mudah alih terutamanya telefon pintar (Miglani & Awadhiya, 2017). Begitu juga, kemahiran guru dalam penggunaan M-pembelajaran dapat dilihat dari aspek penggunaan pelbagai kaedah bagi penilaian pembelajaran (Muniroh, Siti Balqis & Ch'ng, 2020).…”
Section: Kemahiran Guruunclassified